Cryptic sexual populations account for genetic diversity and ecological success in a widely distributed, asexual fungus-growing ant - Rabeling, Christian; Gonzales, Omar; Schultz, Ted R.; Bacci Junior, Mauricio [UNESP]; Garcia, Marcos V. B.; Verhaagh, Manfred; Ishak, Heather D.; Mueller, Ulrich G. (Natl Acad Sciences, 2011)
Sex and recombination are central processes in life generating genetic diversity. Organisms that rely on asexual propagation risk extinction due to the loss of genetic diversity and the inability to adapt to changing environmental conditions. The fungus-growing ant species Mycocepurus smithii was thought to be obligately asexual because only parthenogenetic populations have been collected from widely separated geographic localities. Nonetheless, M. smithii is ecologically successful, with the most extensive distribution and the highest population densities of any fungus-growing ant. Here we report that M. smithii actually consists of a mosaic of asexual and sexual populations that are nonrandomly distributed geographically. The sexual populations cluster along the Rio Amazonas and the Rio Negro and appear to be the source of independently evolved and widely distributed asexual lineages, or clones. Either apomixis or automixis with central fusion and low recombination rates is inferred to be the cytogenetic mechanism underlying parthenogenesis in M. smithii. Males appear to be entirely absent from asexual populations, but their existence in sexual populations is indicated by the presence of sperm in the reproductive tracts of queens. A phylogenetic analysis of the genus suggests that M. smithii is monophyletic, rendering a hybrid origin of asexuality unlikely. Instead, a mitochondrial phylogeny of sexual and asexual populations suggests multiple independent origins of asexual reproduction, and a divergence-dating analysis indicates that M. smithii evolved 0.5-1.65 million years ago. Understanding the evolutionary origin and maintenance of asexual reproduction in this species contributes to a general understanding of the adaptive significance of sex.
Keywords: Attini; clonality; Formicidae; thelytoky; mutualism